SEISMOGENIC ZONE OF CAPE SHARTLAY (LAKE BAIKAL): SPECIFIC FEATURES OF STRUCTURE, DISPLACEMENTS AND RUPTURE GROWTH - O. V. Lunina; I. A. Denisenko; E. B. Ignatenko; A. A. Gladkov (Геодинамика и тектонофизика)
Seismogenic deformations of Cape Shartlay represent a very young fault system on the northwestern coast of Lake Baikal. Their study is providing an important opportunity to measure earthquake magnitudes, to identify areas where earthquakes are more likely to occur, and to estimate the probability of earthquake occurrence as applied to seismically active Baikal region. In this connection, the present work was aimed at characterizing in detail the structure, displacements, and reconstruction of the rupture propagation model. The study is based on photogrammetric processing and interpretation of the unmanned aerial survey data, as well as on morphostructural analysis of the displacement profiles and georadiolocation (GPR) data. It has been found that seismogenic ruptures of Cape Shartlay formed under prevailing extension conditions during no less than two earthquakes with magnitudes Mw≥7.0, Ms≥7.2. Seismic rupture propagation was primarily northward. The main rupture with displacement amplitude of more than 2 m contributed 39 to 93 % to the total surface displacement depending on the amount of dislocations on the transverse profile. It is shown that the length of a certain rupture increased almost instantaneously, then displacements along some of the ruptures stopped. A significant elongation of ruptures is primarily due to their merging. The present-day seismogenic zone is highly permeable. According to the tectonophysical model of formation of inner structure of the fault zone, the development of the seismogenic rupture system of Cape Shartlay corresponds to the late disjunctive stage. This means that the rupturing process in this segment of the North Baikal fault may not have stopped yet, and the lack of large earthquakes in the instrumental record implies the accumulation of stress in its southern part. The obtained results provide an opportunity to reconstruct the development of large fault zones by studying the displacement profiles and, therefore, to localize more precisely the places where future earthquakes may occur.